Validasi Modul: Terapi Kelompok Suportif Ekspresif untuk Menurunkan Depresi pada Wanita yang Mengalami Infertilitas Primer - Khabibah Solikhah; Noor Rachman Hadjam (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2018)
The aim of this study is to examine the validity of Supportive Expressive Group Therapy modules to reduce depression in infertility women. Participants in this research consist of 12 people. The results of validity content through professional judgment obtained that the coefficient of validity Aiken's V moves from 0.58 to 0.92 with a reliability coefficient of 0.972. This indicates that the module has good content validity. While empirical validity testing is done by a quasi-experiment method. The analysis method used nonparametric Mann Whitney U-test. The result of the analysis shows that the value of Z is -2.756 with probability equal to 0.006 (p <0,05). This suggests that there is a significant difference between the level of depression in the control group and the experimental group after receiving supportive-expressive therapy.